Constitutional Design of Strengthening DPR Role in Forming, Changing, and Dissolving State Ministries in the Constitutional Views - Wahyuni, Purwaningdyah Murti; Chandra, M Jeffry Arlinandes; Dinata, Ari Wirya; Illahi, Beni Kurnia; Gusman, Delfina (Nagari Law Review, 2023)
As a country that maintains a presidential system of government, it is essential to concentrate on creating the framework and structure of government. This is closely tied to the establishment, evolution, and dissolution of such institutions. As a consequence, the President and the DPR will be capable of determining responsive and constitutional legal politics. This legal policy study focuses on how the growth and regulation of state ministries and state institutions were connected to the constitutional system's establishment, modification, and dissolution. Second, how can legal politics address this in a manner that seems to be constitutional? The objective of this study is to assess the arrangements pertaining to the formation, alteration, and dissolution of ministries and state institutions under the constitutional system in order to define the ideal political legislation.This research uses normative legal research methods with descriptive research specifications and is analyzed through library research and data analysis methods using juridical-qualitative. The results of the research and discussion in this study include: First, the arrangements regarding the formation, modification, and dissolution of ministries and state institutions do not yet have a clear legal basis so that the President as the holder of power, is irregular in issuing his policies. Second, the legal politics that was initiated wanted the Government and the DPR to be more synergized in terms of drafting legal considerations and normalizing them based on statutory regulations and principles in a presidential system of government.